Developing a Family Planning Counseling Intervention for Women and Adolescent Girls in Resource-Limited Settings - Dev, Rubee (My University, 2018)
University of Washington Abstract Developing a Family Planning Counseling Intervention for Women and Adolescent Girls in Resource-Limited Settings Rubee Dev Chair of the Supervisory Committee: Pamela Kohler School of Nursing Introduction: Unintended pregnancy, including both mistimed and unwanted pregnancies, is associated with negative health outcomes for women and children including maternal depression, increased risk of physical violence, premature deliveries, and low birth weight among children. Adolescents, postpartum, and HIV-infected women are key populations at risk of unintended pregnancy, with unique unmet contraceptive needs. Despite contraceptive guidelines and recommendations, underuse and discontinuation of effective contraception remains a great challenge. The studies within this dissertation address gaps in understanding of contraceptive use behavior and counseling experiences of adolescents and women in resource-limited settings to inform development of FP interventions in Kenya. Methods: To inform contraceptive use behavior of postpartum women, we conducted a systematic literature review and meta-analysis on postpartum contraceptive use, including predictors and barriers among women in resource-limited settings. Using survey data from 109 HIV care and treatment programs in Kenya, we further examined the correlates of receipt of contraceptive counseling among HIV-infected women to determine whether there were differences in who was offered FP services and whether methods offered matched women's preferences. Finally, to improve FP counseling services, we developed an interactive mobile application for contraceptive choice (iMACC) to guide women through the FP decision-making process. We evaluated the feasibility, acceptability, and utility of our FP decision-aid among postpartum adolescent girls and women, as well as FP providers, in Kenya. Results: Through the systematic review, we found an overall pooled prevalence of modern contraceptive use among postpartum women of 41.2%. Low uptake was related to low perceived risk of getting pregnant and inadequate contraceptive counseling. In the surveys of HIV-positive women, those who were already using FP, and those who desired to delay pregnancy more than two years, were more likely to receive FP counseling by their health provider. Married women with higher education and other children were more likely to receive counseling on benefits of birth spacing and limiting. Findings from qualitative interviews support the feasibility, acceptability, and utility of the FP counseling decision-aid to tailor counseling to women's unique needs and facilitate decision-making among women with their FP providers in resource-limited settings. Conclusions: The studies within this dissertation aim to overcome gaps in contraceptive counseling and improve contraceptive use, satisfaction, and continuation among adolescent, postpartum, and HIV-infected women who have unique needs for contraception in resource-limited settings. Uptake of FP services may be improved by providing high quality, individualized FP counseling and by better integrating FP counseling for all women in primary, postpartum, and HIV care.
Thesis (Ph.D.)--University of Washington, 2018
Keywords: Nursing; Nursing